Trends in the population of British wintering ducks 1961-64 - Atkinson-Willes, G L; Frith, J C (Wildfowl, 1965)
The data available through the National Wildfowl Counts are used to keep a running check on the numbers of wildfowl occurring in Britain during the winter months from September to March. Each month a brief report is sent to all observers engaged in the investigation, and it is these which provide the basis of.